KAJIAN NEW HISTORICISM TERHADAP KUMPULAN PUISI MUSEUM PENGHANCUR DOKUMEN KARYA AFRIZAL MALNA - Ibnu Sina Palogai (JURNAL ILMU BUDAYA, 2022)
Abstract New Historicism with its cultural poetry is also referred to as a triad of interpretation that must be studied thoroughly. This view has implications for the practice of interpretation and analysis in literary research. In this case, Greenblatt conveys three steps or a triad: (1) Literary text with assumptions as a manifestation of the author's biographical expression that leads to psychological and ideological aspects. Then, (2) literary works are seen symbolically-structurally as textual codes whose formation is closely related to authorship and sociocultural expressions. Next, (3) reflectively interpret and analyze the codes of literary texts constructed by social forces in the discourse. Keywords: New Historicism, cultural poetry, poetry, Museum Penghancur Dokumen